KEBUTUHAN ASAM LEMAK -3 HUFA DALAM PAKAN UNTUK PERTUMBUHAN JUVENIL KERAPU BEBEK (Cromileptes altivelis) - Muhammad Marzuqi; Nyoman Adiasmara Giri; Ketut Suwirya (Jurnal Perikanan Universitas Gadjah Mada, 2005)
ω-3 HUFA are essential fatty acids for marine fish. Deficiency of these essential fatty acids is responsible for high mortality, low growth rate, incomplete formation and disfunction of swim bladder. This experiment was conducted to know dietary ω-3 HUFA requirement for growth of humpback  grouper juveniles.  Juveniles (9.8-10.3  g) were reared in 100 l of polycarbonate  tank with density of 12 juveniles/tank for 8 weeks with flow through system. The levels of ω-3 HUFA (EPA +DHA) supplementation in the test diet  were 0.0, 0.5, 1.0, 1.5, 2.0  and 3.0%. The results showed that the levels of ω-3 HUFA affected the growth and feed efficiency of humpback grouper juveniles (P<0.05). The growth of juveniles fed diet with 0.0-3.0% ω-3 HUFA were  significantly different with the growth of juveniles fed diet with 0.0 and 0.5% ω-3 HUFA. The growth of juveniles fed diet with supplementation levels of ω-3 HUFA at 1.0,  1.5,  2.0,  and 3.0% were 182.2, 168.5, 183.4, and 189.4%, respectively. Whereas supplementation of  ω-3 HUFA at 0.0 and 0.5% resulted the growth of  114.9 and 139.6%, respectively. These results indicated that the requirement of ω-3 HUFA for growth of humpback grouper should be around 1.0% in diet.ω